Physical Education Teachers' Attitudes Towards Stimulating Higher Order Thinking Skills in Elementary School Students: Differences in Certified and Non-Certified Teachers - Sefri Hardiansyah; Nurlan Kusmaedi; Amung Ma'mun; Agus Mahendra (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
Elementary school-age children have started thinking logically and rationally; therefore, they need to be stimulated to think in a higher order. Higher-order thinking skills (HOTS) can help students think critically and creatively, solve problems and find solutions. Therefore, physical education teachers must participate in stimulating students' HOTS. This research aims to determine differences in physical education teachers' attitudes (certified and non-certified) based on gender, age and length of service toward HOTS stimulation in students. The method used in this research is comparative. The research sample consisted of certified and non-certified physical education teachers who taught in elementary schools in West Sumatra province, Indonesia, with 105 people (male = 77 and female = 28) aged 23-59 years. They were selected using accidental sampling. The instrument to measure stimulating higher-order thinking skills uses a Likert scale questionnaire consisting of 16 items. Data analysis was carried out using the Mann-Whitney U Test and Kruskal-Wallis H. The results of the study showed that differences in the attitudes of certified and non-certified teachers obtained a p-value < .05, while comparisons based on gender, age and work experience had a p-value> .05. So it can be concluded that the attitudes of certified and non-certified teachers towards HOTS stimulation are significantly different, while based on gender, age and length of service their attitudes towards HOTS stimulation are not significantly different.